Algol procedures for range arithmetic - Gibb, Allan (1961)
Algorithms are written (and tested on the Burroughs 220) for the execution of the fundamental arithmetic operations in range arithmetic for real and for complex arguments. These algorithms are translated into the international algorithmic language ALGOL 60. An illustration is presented of an application to the problem of bounding a zero of a polynomial, given an estimate of the zero. (Author).
Keywords: Complex variables; Errors; Series(mathematics)